2020
DOI: 10.3390/en13174568
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Approach to the Steady-State Efficiency Analysis of Torque-Adding Transmissions Used in Renewable Energy Systems

Abstract: The paper presents a general approach to the steady-state efficiency analysis of one degree of freedom (1-DOF) speed increasers with one or two inputs, and one or two outputs, applicable to wind, hydro and marine-current power generating systems. The mechanical power flow, and the efficiency of this type of complex speed increasers, are important issues in the design and development of new power-generating systems. It is revealed that speed increases, with in-parallel transmission of the mechanical power from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The in-parallel transmission of mechanical power from inputs to outputs can be achieved by power split at input, output or both, which ensures a higher efficiency compared to transmissions obtained by serial connection of the same component mechanisms [48]. A new approach to the development of modern wind turbines is the use of two counter-rotating coaxial rotors and the integration of a counter-rotating electric generator, which requires a mechanical transmission with power split at both input and output.…”
Section: Problem Formulationmentioning
confidence: 99%
“…The in-parallel transmission of mechanical power from inputs to outputs can be achieved by power split at input, output or both, which ensures a higher efficiency compared to transmissions obtained by serial connection of the same component mechanisms [48]. A new approach to the development of modern wind turbines is the use of two counter-rotating coaxial rotors and the integration of a counter-rotating electric generator, which requires a mechanical transmission with power split at both input and output.…”
Section: Problem Formulationmentioning
confidence: 99%
“…A general approach to the steady-state efficiency analysis of speed increasers with both one or two inputs and one or two outputs is proposed in [31]. The authors concluded that the in-parallel or split-power transmissions used in wind turbines with either two counter-rotating rotors or a counter-rotating generator have higher efficiency than serial transmissions.…”
Section: Introductionmentioning
confidence: 99%
“…Various innovative solutions of planetary speed increasers were proposed (Saulescu et al, 2016b;Saulescu et al, 2018;Neagoe et al, 2019) for counterrotating WECS. The performance in the steady-state regime of the different WECS configurations was investigated comparatively (Saulescu et al, 2016b;Neagoe et al, 2019;Saulescu et al, 2021;Neagoe and Saulescu, 2022), and a generalized approach for the efficiency analysis of 1-DOF speed increasers for counter-rotating WECS was proposed (Neagoe et al, 2020).…”
mentioning
confidence: 99%
“…Recent research proved that the use of the counter-rotating generators can lead to a higher conversion efficiency of WECS than the conventional system (Saulescu et al, 2016a; Frontiers in Energy Research 02 frontiersin.org Saulescu et al 10.3389/fenrg.2023.1215509 2016b; Neagoe et al, 2017;Neagoe et al, 2019;Neagoe et al, 2020;Saulescu et al, 2021;Neagoe and Saulescu, 2022). However, only a few studies analyzed WECS configuration with both counterrotating rotors and counter-rotating generator and proposed suitable mechanical transmissions (Neagoe et al, 2019;Neagoe et al, 2020;Neagoe and Saulescu, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation